Sharing the risk at expense of power : Paying wages in equity to face the COVID-19 - Aubert, Nicolas; Córdova, Miguel (Pontificia Universidad Católica del Perú. Departamento Académico de Ciencias de la Gestión, 2020)
This paper aims to discuss which basic implications firms need to be aware of if they decide to include equity shares as a part of salary payments in order for them to tackle financial risks due to the COVID-19 crisis, benefiting with better liquidity. We discuss this alternative from the strand of potential financial benefits, but also include a power perspective, emphasizing how firms could share with employees their decision-making processes as well as a part of their position of traditional hegemony. We concluded that firms’ decision regarding this financial alternative fits into a short-term benefit and at the same time threats a long run position of power.
Keywords: COVID-19 (Enfermedad); Coronavirus; Financial crisis; Equity payment; Recession; Cashflow; Firm ownership; http://purl.org/pe-repo/ocde/ford#5.02.04